Temporal and Topographic Matrix Metalloproteinase Expression after Vascular Injury in Mice - Lijnen, H. R.; Lupu, F.; Moons, L.; Carmeliet, P.; Goulding, D.; Collen, D. (Thrombosis and Haemostasis, 1999)
Temporal and topographic expression of matrix metalloproteinases (MMPs) after perivascular electric injury was studied in wild-type (WT) and urokinase-deficient (u-PA-/-) mice. Neointima formation after injury of the femoral artery was significantly reduced in u-PA-/- mice as compared to WT mice (area of 0.002 ± 0.0007 mm2 versus 0.008 ± 0.002 mm2 at 3 weeks after injury; p <0.001), associated with impaired cellular migration (nuclear cell counts of 44 ± 5 versus 82 ± 9 in cross-sectional areas; p <0.001).Zymographic and/or microscopic analysis indicated that MMP expression gradually increased to reach a maximum at 1 to 2 weeks after vascular injury. In general, MMP levels were lower in u-PA-/- than in WT mice. In non-injured arteries, MMP-2 (gelatinase A) and MMP-3 (stromelysin-1) were produced mainly by adventitial fibroblasts and/or non-contractile smooth muscle cells (SMC). One week after injury, MMP-2 and MMP-3 levels were enhanced due to an increased number and size of producing cells; 2 to 3 weeks after injury, MMP-2 and MMP-3 were produced also by some contractile SMC, which stained with α-actin antiserum. MMP-9 (gelatinase B), MMP-12 (metalloelastase) and MMP-13 (collagenase-3) were found in macrophages located mainly in the adventitia. Immunogold electron microscopic examination revealed that MMP-2 was located predominantly in association with the cell surface of fibroblasts or SMC, while MMP-9 and MMP-12 were located in well defined storage granules within macrophages. MMP-2, MMP-3 and MMP-13, but not MMP-9 or MMP-12, were also found extracellularly, associated with elastin-containing structures (MMP-2), with the basement membrane and occasionally with collagen fibres (MMP-3), or with proteoglycans, collagen and elastin (MMP-13).The temporal and topographic expression pattern of MMPs after vascular injury, coinciding with smooth muscle cell migration and neointima formation, thus is compatible with a role in vascular remodeling.